Seismic dispersion and attenuation in saturated porous rocks with aligned fractures of finite thickness: Theory and numerical simulations - part 1: P-wave perpendicular to the fracture plane - Guo, J.; Rubino, J.; Barbosa, N.; Glubokovskikh, Stanislav; Gurevich, Boris (Society of Exploration Geophysics, 2018)
When a seismic wave travels through a fluid-saturated porous reservoir containing aligned fractures, it induces oscillatory fluid flow between the fractures and the embedding background medium. Although there are numerous theoretical models for quantifying the associated seismic attenuation and velocity dispersion, they rely on certain assumptions, such as infinitesimal fracture thickness and dilute fracture concentration, which rarely hold in real reservoirs. The objective of this work is to overcome some of these limitations and, therefore, improve the applicability of the available theoretical models. To do so, we extend existing models to the finite fracture thickness case for P-waves propagating perpendicular to the fracture plane using the so-called branching function approach. We consider three types of fractures, namely, periodically and randomly spaced planar fractures, as well as penny-shaped cracks. The extended unified model is then tested by comparing with corresponding numerical simulations based on Biot's theory of poroelasticity. We consider two cases of 2D rock samples with aligned elliptical fractures, one with low fracture density and the other with high fracture density. The results indicate that the influence of the finite fracture thickness on seismic dispersion and attenuation is small at low frequencies when the fluid pressure has enough time to equilibrate between the fractures and background medium. However, this effect is significant at high frequencies w hen there is not sufficient time for the fluid pressure equilibration. In addition, the theoretical predictions of the pennyshaped crack model are found to match the numerical simulation results very well, even under relatively high fracture density. Analyses of stress distributions suggest that the small discrepancies found between theoretical predictions and numerical simulations are probably due to fracture interactions. In a companion paper, we will extend the analysis for considering the full stiffness matrix and anisotropic properties of such rocks.